Penerapan Diabetes Self-Management Education (DSME) terhadap Manajemen Kesehatan Keluarga di Desa Sungai Putih Kec. Tapung Kab. Kampar - Nurul Afni; Candra Saputra; Emul Yani; Donny Hendra (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
. Indonesia ranks 7th with the number of DM patients as many as 10.7 million people and this number is expected to continue to increase every year. Diabetes mellitus is a complex disease that requires making many decisions every day about eating, physical activity and medication, also requires patients to be proficient in a number of self-management skills. Low knowledge in self-management of DM sufferers causes various complications. The purpose of the Final Scientific Paper for Nurses is to provide an overview of the results of the practice of the Nursing Profession with the Application of Family Nursing Care with the Implementation of Diabetes Self-Management Education (DSME) Against the Problem of Ineffective Family Health Management Nursing in Sungai Putih Village, Tapung District, Kampar Regency. The method used in implementing nursing interventions is the provision of Diabetes Self-Management Education (DSME). The advantages of Diabetes Self-Management Education (DSME) for families and patients are to increase knowledge and awareness, develop skills in managing diabetes mellitus, improve quality of life, and improve decision-making skills. The provision of Diabetes Self-Management Education (DSME) is carried out for 3 meetings. The results of this case study after conducting 3 meetings of Diabetes Self-Management Education (DSME) obtained an average value of increasing family health management towards the implementation of Diabetes Self-Management Education (DSME) before the intervention was given on the first day, namely 9.5 (average value of SLKI) and after being given intervention for three consecutive days, namely the final value obtained was an increase in family health management towards the implementation of Diabetes Self-Management Education (DSME) 33 (average value of SLKI) there was a significant increase.